Pengaruh Big-Five Personality dan Environmental Sensitivity terhadap Responsible Environmental Behavior Siswa - Ade Imas Rismayati; I Made Putrawan; Diana Vivanti (IJEEM - Indonesian Journal of Environmental Education and Management, 2019)
Environmental problem is a problem that must be solved by all parties, including students. Responsible environmental behavior arises from awareness of environmental issues. This awareness led to intention and determination of student to set their attitude and behavior towards the problems they faced. Responsible environmental behavior is basically the result of interaction between various factors. Factors that may affect the responsibilities behavior among the personality and the environmental sensitivity. This study aims to determine the effect of personality and environmental sensitivity on the responsible environmental behavior that students have. Research conducted at SMA Labschool Jakarta on the Semester I of 2018/2019 school year. The method used is the survey with quantitative-causal causal approach and path analysis. The sample were 79 students of class XI MIPA. Based on hypothesis test, the value of the path coefficient of X1 to X2 is 0.495, path coefficient X2 to X3 is 0.028, and path coefficient X1 to X3 is 0.568 but the path coefficient X1 to X3 through X2 cannot be calculated. Based on these results, it can be concluded that environmental sensitivity is not suitable as a mediator of variables between personality and responsible environmental behavior. Keywords: Personality, environmental sensitivity, responsible environmental behavior.